Representasi Ketimpangan Gender dalam Film Wadjda karya Haifa : Kajian Feminisme Marxis Sosialis - Az Zahra Farhatu Niswah; Yayan Rahtikawati; Khomisah Khomisah (Universitas Palan, 2026)
This study examines the representation of gender inequality and forms of women's resistance in Haifaa al-Mansour's film Wadjda using a Marxist-Socialist feminist perspective. This study aims to identify the forms of gender inequality represented in the film and analyze the forms of resistance carried out by female characters against the patriarchal structure in Saudi Arabian society. The research method used is a descriptive analytical method with a qualitative approach. Research data were obtained through observation and note-taking techniques of dialogue, scenes, and visual elements in the film related to gender issues and women's resistance. The results of the study indicate that there are four forms of gender inequality in the film, namely restrictions on women's roles, women's lack of freedom in behavior, patriarchal acts, and claims of culture and Islamic norms of Saudi Arabian society that are used to legitimize women's subordination. In addition, this study also found several forms of resistance carried out by female characters, especially Wadjda, such as the desire to own a bicycle, independent economic strategies, negotiations with school authorities, unconventional expressions of identity, and covert resistance shown by Wadjda's mother.